Practice and Challenges of Rehabilitation Treatment for Children in Need of Upper Limb Prosthetics: Parents Survey - Alina S. Kuzyakina; Maria V. Avxentyeva ("Paediatrician" Publishers LLC, 2020)
Background. Upper limb prosthetics can be required in many conditions, and congenital as well. The situation in Russian healthcare system with rehabilitation of children with upper limb prosthetics has not been studied before.Objective. The aim of the study was to study current situation and challenges in rehabilitation of children in need of upper limb prosthetics due to congenital diseases.Methods. The simultaneous qualitative research was performed - in depth semi-structured interview of parents whose children had got active prosthetics of upper limbs due to congenital diseases in the period from October 2017 to April 2018. There were 8 open-ended questions and 13 closed-ended question in the interview about availability and timeliness of rehabilitation, complexity and personality of the approach, observance of the phasing and continuity principles, and also involvement into rehabilitation process. The interview was performed after obtaining of the active prosthetic.Results. 20 parents of children aged from 2 to 17 years from 8 regions of Russian Federation have undergone the survey. Only 75% of children undergone rehabilitation treatment over the years (before prosthetic positioning), and 93% of them only during the first phase (in health resort institution). Active prosthetic was delayed in 90% of cases. The complex and individual approach to rehabilitation was disrupted in 75% of cases. The child and his family were not actively involved in rehabilitation process in all cases. All respondents have mentioned low availability of rehabilitation. Most of the parents (80%) mentioned as well that they have to pay their own money to cover all the expenses.Conclusion. The interview of parents whose children are in need of active prosthetic revealed that one in four child did not get rehabilitation treatment. In cases when rehabilitation had been carried out many imperfection in its organization were identified. Low awareness about rehabilitation itself among parents and low interest in changing of the existing rehabilitation system were revealed.